Post-Graduate Students' Perceptions Regarding Effectiveness of Mentoring Relationship at Universities - Karakose, Turgut; Yirci, Ramazan; Uygun, Harun; Ozdemir, Tuncay Yavuz (Expert Projects Publishing, 2016)
The purpose of this study is to examine the effectiveness of mentoring relationship between faculty members and post-graduate students according to various variables. The sample consists of 99 post-graduate students studying at public universities in Turkey. The Mentoring Effectiveness Scale, developed by Berk, Berg, Mortimer, Walton-Moss, and Yeo (2005) and adapted into Turkish by Yirci, Karakose, Uygun, and Ozdemir (2016) was used as the data collection instrument. According to the study findings, post-graduate students in general find the effectiveness levels of mentoring relationships in universities sufficient. Accordingly, it is suggested that the frequency of mentor and mentee meetings should increase. While the effectiveness of mentoring relationship is not affected by age and gender variables; it is influenced by the frequency of meetings and the meeting method preferred. Study findings also suggest that mentees expect to be appreciated more than the mentors.
Keywords: mentoring effectiveness; postgraduate students; mentor; mentee